Colombia : Financial Sector Assessment Program-Report on the Observance of Standards and Codes on FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report, 2018)
Colombia has a reasonable understanding of its main domestic money laundering/terrorist financing (ML/TF) risks. The country's understanding of risks relies particularly on the results of the 2013 and 2016 National Risk Assessments (NRAs). -- The 2016 NRA has yielded reasonable findings with respect to the identification of the main ML threats and vulnerabilities. -- The AML/CFT supervisory systems and tools are not entirely in line with the risk-based approach (RBA), and there are significant gaps in the supervision of designated non-financial businesses and professions (DNFBPs). -- Colombia investigates and prosecutes ML effectively, but not in a manner that is commensurate with its ML risks.